Pengaruh disiplin, motivasi dan stress kerja terhadap kinerja pegawai Dinas Ketenagakerjaan Provinsi Sumatera Utara - Joko Pramono; Akman Daulay; Windy Aginta (Fakultas Ekonomi Universitas Al-Azhar Medan, 2026)
The aim of thisI research is to findI out how discipline, motivation and work stress influence theI performanceI ofI NorthI SumatraI Province ManpowerI Service employees. This research uses quantitative research methodology. Questionnaires, documentation studies, and observations are the methods used to collect data. Employees of the North Sumatra Province Employment Service are the research population, whose address is Jl. Dormitory No. 143 Medan – 20126. with a total of 70 employees. The author took the total population in the North Sumatra Provincial Employment Service office as 70 employees using a saturated sampling technique which will be used as the sample in this research. Therefore, the census approach is the use of the entire population as a unit of observation when it is not necessary to take a research sample. Based on research findings, discipline has a significant and positive effect on worker performance. The performance of North Sumatra Province Manpower Service employees is influenced positively and significantly by motivation. Stress at work has a detrimental and negligible impact on the performance of North Sumatra Province Manpower Service workers. The results of the research state that Fcount (36.809) > Ftable (2.74), andI the Isignificant Ivalue is 0.000 < 0.05, so iIt canI be said that the fourth hypothesis is supported which shows that the performance characteristics of North Sumatra Province Manpower Service employees are influenced simultaneously by discipline, motivation and work stress factors